2008
DOI: 10.1136/hrt.2008.150474
|View full text |Cite
|
Sign up to set email alerts
|

Radial artery anomaly and its influence on transradial coronary procedural outcome

Abstract: Anomalous radial artery anatomy is relatively common and is a significant cause of procedural failure. Within each specific anomalous pattern there is a differential procedural failure rate. This has implications for clinical practice and suggests a need for imaging of the radial artery after sheath insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
158
2
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(173 citation statements)
references
References 23 publications
6
158
2
7
Order By: Relevance
“…Lo et al (19) recently studied 1,540 consecutive radial procedures and found radial artery anomaly in 13.8% patients while Valsecchi et al (20) has reported quite a high incidence as 22.8% in his study of 2, 211 cases. In our study, atypical anatomy was found 21.1% in r-CA group while it was 11% in f-CA group (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Lo et al (19) recently studied 1,540 consecutive radial procedures and found radial artery anomaly in 13.8% patients while Valsecchi et al (20) has reported quite a high incidence as 22.8% in his study of 2, 211 cases. In our study, atypical anatomy was found 21.1% in r-CA group while it was 11% in f-CA group (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Their incidence may vary according to the available literature, starting from 8,8% [7,6], 13,8% [2], up to 22,8% according to Valsecchi et al [3]. They can be reason for procedural failure in 1-5% of the patients even in experienced operators` hands [4,9].…”
Section: Discussionmentioning
confidence: 99%
“…Its advantages over the transfemoral approach (TFA) are clear and include reduced risk of access-site complications (bleeding), early patient ambulation, better patient comfort, reduced costs for hospitalization and possibility for same day discharge [1][2][3][4][5]. On the other side, TRA can be very challenging in comparison to TFA demanding better operators` skills, especially in cases of different anatomical variations and anomalies of the forearm`s vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…Transradial procedure failures can sometimes be due to variation in the radial artery anatomy. 17 This has implications for clinical practice and suggests a need for imaging of the radial artery before such procedure.…”
Section: 11mentioning
confidence: 99%